Exploring the potent enhancement effects of plyometric training on vertical jumping and sprinting ability in sports individuals - Xie, Lin; Chen, Jiayong; Dai, Jing; Zhang, Wenfeng; Chen, Lunxin; Sun, Jian; Gao, Xiang; Song, Junyi; Shen, Hailun (Frontiers in Physiology, 2024)
Objective: This meta-analysis examines the impact of different combinations of plyometric training (complexity, training volume, and rest intervals) on immediate vertical jump and sprint performance in athletes. Methods: A systematic search was conducted in four databases, and Cochrane guidelines were used to evaluate the quality of included studies. Review Manager 5.4 software was employed to analyze outcome measures. Nineteen randomized controlled trials involving 293 participants were included. Results: Single plyometric training-induced post-activation potentiation (PAP) had a slight positive effect on vertical jump performance (SMD=-0.24, 95% CI (-0.38, -0.1), P=0.0009). Optimal results were observed with rest intervals of 0.3 to 4 minutes (SMD=0.30, P=0.0008). Sprint performance showed slight improvement (SMD=0.27, 95% CI (0.03, 0.52), P=0.03). Complex plyometric training had a moderate effect on vertical jump performance (SMD=0.58, 95% CI (-0.86, -0.23), P=0.002), with the best outcomes seen with rest intervals exceeding 8 minutes (SMD=0.77). Sprint performance also improved significantly (SMD=0.8, 95% CI (0.01, 1.59), P=0.05). Single-session plyometric training did not significantly enhance vertical jump performance (SMD=-0.19, 95% CI (-0.41, -0.02), P=0.07), but had a notable effect on sprint performance (SMD=0.8, 95% CI (0.01, 1.59), P=0.05), particularly with rest intervals exceeding 8 minutes (SMD=0.77). Multiple-session plyometric training improved vertical jump (SMD=0.43, 95% CI (0.01, 1.59), P=0.00001<0.05), with optimal effects observed at rest intervals of 5 to 7 minutes (SMD=0.64). Sprint performance also improved (SMD=0.46, 95% CI (0.01, 0.81), P=0.01<0.05).Plyometric training as an activation method has significant enhancing effects, depending on training complexity, volume, and rest intervals.